Turning intercalators into groove binders: synthesis, photophysics and DNA binding properties of tetracationic mononuclear ruthenium(ii)-based chromophore–quencher complexes. Issue 35 (16th August 2018) - Derrat, Hanan S.; Robertson, Craig C.; Meijer, Anthony J. H. M.; Thomas, Jim A.
Abstract : Despite incorporating an extended planar polyaromatic ligand two newly synthesized Ru II complexes are not DNA intercalators but groove binders. Abstract : The synthesis of two new tetracationic mononuclear Ru II complexes containing the tetrapyridyl [3, 2- a :2′, 3′- c :3′′, 2′′- h :2′′′, 3′′′- j ] phenazine ligand in which the uncoordinated site has been converted into a dicationic ethylene-bipyridyldiylium unit is reported. The structure of the complexes is fully assigned through detailed NMR studies and, in one case, through an X-ray crystallography study. Voltammetry, optical spectroscopy and computational studies confirm that the bipyridyldiylium moiety has a low-lying reduction that quenches the 3 MLCT-based emission usually observed in such systems. The new complexes interact with DNA in a quite different manner to their dicationic analogues: they both bind to duplex DNA with micromolar affinity through groove binding. These observations are rationalized through a consideration of their structural and electronic properties.